51. BRAIN METASTASES FROM ENDOMETRIAL CARCINOMA: TUMOR GENETIC ALTERATIONS IN A CASE SERIES AND META-ANALYSIS. (4th August 2020) - Chapman, Emily K; Tsankova, Nadejda; Sebra, Robert; Germano, Isabelle M
Abstract: INTRODUCTION: Endometrial carcinoma (EC) is the most common gynecologic malignancy in the world. While most patients (80%) can be cured with a hysterectomy, the remaining 20% patients who are diagnosed with advanced or recurrent disease have worse survival rates and limited adjuvant treatment options. Discovery of novel target(s)/pathway(s) is needed for better understanding of the pathogenesis and treatment development for this disease. The aim of this study is to review clinical characteristics and genetic signatures of histologically proven EC brain metastasis (BM). METHODS: For the period 2000–2019 the medical records of patients with histological diagnosis of EC BM at our Institution were reviewed. Data were collected and analyzed for age, time interval between EC and EC BM diagnoses, tumor molecular and genetic signatures, and outcome. Immunohistochemistry and sequencing performed as published. A meta-analysis was also performed for the same time period. Data presented as mean+SD and analyzed by t-test and Chi square. RESULTS: There were 6 BM from 5 patients meeting our cohort entry criteria and a total 123 cases reported in the literature. The mean age was 57.6 + 11.7 (range 39–69) consistent with reported data. The time interval between EC and EC BM diagnoses was 145.7 + 119.7 (range 33.1–275.7), significantly longer than reported (19.4 + 27.8; range 0–156; p<0.05). All BM in our cohort were metachronous, while only 59% were in the literature. Whereas all FIGO grades are reported in the literature (I=20%; II=6%; III=42%; IV=32%), only I and III were found in our cohort (I=60%, III=40%). Tumor microsatellite instability genes MSH2 and MSH6 were intact, whereas MLH1 and PMS2 showed mutations. PD-L1 expression was low. EC BM genomic reports were not found in the literature. CONCLUSIONS: Our study provides insight into the genomic alteration burden on EC BM. Information-driven genomic testing will continue to lead patient-centered therapeutic approaches.